2015
DOI: 10.1093/chemse/bjv050
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Odorant Binding Proteins and Chemosensory Proteins in Antennal Transcriptomes of the Jumping BristletailLepismachilis y-signataand the FirebratThermobia domestica:Evidence for an Independent OBP–OR Origin

Abstract: Chemosensory protein (CSP) and gustatory receptor genes have been identified in all major arthropod groups. However, odorant binding proteins (OBP) and olfactory receptor genes are insect specific, suggesting that both gene families originated after the Hexapoda-Crustacea split (~470 million years ago). The seemingly parallel diversification of OBP and olfactory receptors has been suggested as coevolution between these genes after insect terrestrialization. To test this hypothesis we used the recently publishe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 62 publications
2
30
0
Order By: Relevance
“…The greater numbers found in Collembola, with respect to the other two classes simply reflects the greater attention given to this group to date. Similarly, transcriptome studies of Lepysmachilis (order Archaeognatha) and Thermobia (order Zygentoma) identified 40 and 32 OBP genes, and three and six CSP genes, respectively (Missbach et al, 2015). Such relatively large numbers of soluble olfactory proteins indicate that extensive duplication and differentiation must have taken place in basal Hexapoda, especially for OBPs, while CSPs expansion may be limited to Collembola.…”
Section: Figmentioning
confidence: 96%
See 1 more Smart Citation
“…The greater numbers found in Collembola, with respect to the other two classes simply reflects the greater attention given to this group to date. Similarly, transcriptome studies of Lepysmachilis (order Archaeognatha) and Thermobia (order Zygentoma) identified 40 and 32 OBP genes, and three and six CSP genes, respectively (Missbach et al, 2015). Such relatively large numbers of soluble olfactory proteins indicate that extensive duplication and differentiation must have taken place in basal Hexapoda, especially for OBPs, while CSPs expansion may be limited to Collembola.…”
Section: Figmentioning
confidence: 96%
“…During evolution, both OBPs and CSPs seem to have undergone much duplication and differentiation in Hexapoda similarly to ORs that evolved in insects after the emergence of Archaeognatha and Zygentoma (Missbach et al, 2014).…”
Section: (3) Obps and Csps Across Evolutionmentioning
confidence: 99%
“…By using similar methods as for OBP identification, many CSPs have been discovered in distinct insects (Guo et al, 2011; Iovinella et al, 2013; Jacquin-Joly et al, 2001; Liu et al, 2010; Missbach et al, 2015; Picimbon et al, 2001; Wanner et al, 2004). Unlike OBPs, CSPs are smaller and more conserved in distinct insects, which only have four conserved cysteines that form two interlocking disulphide bridges (Bohbot et al, 1998; Lartigue et al, 2002; Maleszka & Stange, 1997; Pelosi, Calvello & Ban, 2005; Zhang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In the case of GRs and ORs, sequences from the waterflea Daphnia pulex were also included as an outgroup (Peñalva-Arana et al, 2009). For the CSPs and OBPs we included sequences from the Jumping Bristletail Lepismachilis y-signata and the Firebrat Thermobia domestica (Missbach et al, 2015). In the case of IRs (and Glu-Rs) sequences from Drosophila melanogaster have been included (Rytz et al, 2013).…”
Section: Alignments and Phylogenetic Treesmentioning
confidence: 99%
“…CSPs are likely to perform similar roles in chemical communication of insects as OBPs, but unlike these are also expressed in non-chemosensory tissues, and for this reason have been hypothesized to serve additional, as yet undiscovered, functions (Pelosi et al, 2005). Recent evidence suggests that OBPs are an adaptation to the detection of hydrophobic volatiles that became available as olfactory cues in the course of insect terrestrialization (Missbach et al, 2015); however, results in Drosophila suggest a different function for some OBPs (Larter et al, 2016). Structurally, insect OBPs and CSPs generally contain α-helical domains, but folded in two different patterns (Sandler et al, 2000;Lartigue et al, 2002;Tegoni et al, 2004).…”
Section: Introductionmentioning
confidence: 99%